A Comprehensive Analysis of Solvency, Profitability, and Liquidity in Minimizing Bankruptcy and Financial Stress - Rejimon, A.V.; Sinosh, P. K.; Krishnaveni, V. (Indian Journal of Finance, 2025)
Purpose : This research examined a firm’s liquidity, profitability, solvency, and cash position to determine their effects on financial distress and potential bankruptcy. It aimed to determine early warning signs and offered insights into financial management practices that can minimize financial distress and improve overall economic well-being. Methodology : Using data from 2014 to 2023, we evaluated the financial distress and insolvency risk of a publicly traded government manufacturing firm. The research utilized the Springate model and the logit probability model to determine the probability of distress during this period. This systematic analysis provided a clear picture of the firm’s financial health and risk of bankruptcy. Findings : The Springate model revealed the company to be financially sound for 10 years. However, the logit probability model reflected a bankruptcy risk over the past three years. The study also highlighted weaknesses in the solvency and liquidity positions of the company. Practical Implications : The results added to theoretical wisdom and offered practical suggestions for reducing insolvency and bankruptcy risk. They also indicated methods to ensure financial stability. Originality/Value : The majority of empirical research has focused on industry-specific liquidity distress with statistical measures. Unlike this, the present study utilized multiple discriminant analyses and applied financial models directly to a specific government-owned company. This method identified corrective measures specifically. Interestingly, very little research has been conducted on assessing the financial distress of government companies in India, so the current study is relevant in providing company-specific findings.